'They needed the attention more than I did': How do the birth children of foster carers experience the relationship with their parents?. (July 2018) - Adams, Emma; Hassett, Alexander R; Lumsden, Virginia
Research has highlighted the potential tensions and risk of disruption to care placements when foster carers have birth children living at home. Given the limited research attention given to these young people and the importance of retaining carers, it seems important for policy and practice to investigate the parent–child relationship in this context. Therefore, this study seeks to explore how the birth children of foster carers experience their relationship with their parents. Interpretative phenomenological analysis was used to analyse semi-structured interviews with eight such young people (aged 14–16 years). Three superordinate themes emerged: (1) relational processes that give value to my role in the family; (2) threats to our relationship; and (3) making sense as a way of managing the threats. Each of these contained several subthemes. While there were consistent patterns of experience, there was also individual variation. The findings suggest that the processes of 'making sense' and 'feeling valued' serve to buffer the impact of potential threats to the parent–child relationship. Theoretical implications include the application of a model that elucidates the relationship between the themes. This has clinical implications for understanding and informing the way services support both foster carers and their children.